Human Immunodeficiency Virus-Associated Nephropathy in Pregnancy - Nancy L. Eriksen; Joan M. Mastrobattista (Hindawi Limited, 1996)
Background: Human immunodeficiency virus (HIV)-associated nephropathy typically leads to endstage renal disease requiring dialysis within 3-4 months. This report describes the prenatal course of a patient with HIV-associated nephropathy requiring dialysis during pregnancy.